2012
DOI: 10.12934/jkpmhn.2012.21.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School Adjustment on Higher Grade Elementary School Students' Internet Game Addiction: Focused on Gender Difference

Abstract: Purpose: The purpose of this study was to investigate factors predicting internet game addiction in higher grade elementary schoolers by gender in a city. Methods: The participants were 356 elementary school students who were in the 5th or 6th grade. Data were collected by structured questionnaires from March 15 to May 10 2011, and analyzed using descriptive statistics, x 2 -test, t-test, ANOVA, Pearson correlation coefficients, and stepwise multiple regression with the SPSS/WIN 17.0 program. Results: Prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…Studies have shown that adolescents whose school life is satisfactory are less likely to develop Internet addiction (Y.-R. Kweon & Kim, 2014;Rehbein & Baier, 2013). Kweon and Park (2012) have reported that adoption of school rules and having good relations with peers and teachers are an important protective factor against Internet addiction in children (Kweon & Park, 2012). In our study, children who don't go to school, despite being at the school age, had higher Internet addiction scores in line with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that adolescents whose school life is satisfactory are less likely to develop Internet addiction (Y.-R. Kweon & Kim, 2014;Rehbein & Baier, 2013). Kweon and Park (2012) have reported that adoption of school rules and having good relations with peers and teachers are an important protective factor against Internet addiction in children (Kweon & Park, 2012). In our study, children who don't go to school, despite being at the school age, had higher Internet addiction scores in line with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…While the score for school life adjustment rarely differed with the odds ratio of 1.04 between the group at risk of Internet game addiction and the non-addiction group, the inter-group mean difference was statistically significant. This supports the finding that the lower the level of school life adjustment and the greater the difficulty with peer relationships, the higher the risk of Internet game addiction [7,10].…”
Section: Journal Of Health Informatics and Statisticssupporting
confidence: 83%
“…According to research on the Internet addiction status for adolescents, as released by a South Korean government agency in 2012, adolescents in multicultural families (12.3%) were more likely to become addicted to Internet than adolescents in general (10.7%) while elementary school children (30.1%) were more likely to become addicted to Internet than middle school students (25%). In particular, Internet-related problems for elementary school children in the transition period from childhood to adolescence can cause social maladjustment, which involves anxiety, frustration, and fear, as well as problem behaviors [6] and become chronic, unless treated properly, which may lead to juvenile delinquency [7]. It is therefore necessary to conduct research on the possibility of Internet games addiction among elementary school children who start to use Internet; in particular, it is necessary to investigate the risk of Internet game addiction among children in multicultural families with the objective of preventing and managing Internet game addiction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous researches investigated factors associated with game addiction at individual‐level (e.g., Ko, Yen, Chen, Chen, & Yen, ). Some studies examined school‐related factors, but the data were also analysed at individual‐level (e.g., Kweon & Park, ).…”
Section: Individual‐level Characteristics and Game Addictionmentioning
confidence: 99%